Delamination of cells from neurogenic placodes does not involve an epithelial-to-mesenchymal transition. - Graham, A; Blentic, A; Duque, S; Begbie, J (2007)
Neurogenic placodes are specialized regions of embryonic ectoderm that generate the majority of the neurons of the cranial sensory ganglia. Here we examine in chick the mechanism underlying the delamination of cells from the epibranchial placodal ectoderm. We show that the placodal epithelium has a distinctive morphology, reflecting a change in cell shape, and is associated with a breach in the underlying basal lamina. Placodal cell delamination is distinct from neural crest cell delamination. In particular, exit of neuroblasts from the epithelium is not associated with the expression of Snail/Snail2 or of the Rho family GTPases required for the epithelial-to-mesenchymal transition seen in neural crest cell delamination. Indeed, cells leaving the placodes do not assume a mesenchymal morphology but migrate from the epithelium as neuronal cells. We further show that the placodal epithelium has a pseudostratified appearance. Examination of proliferation shows that the placodal epithelium is mitotically quiescent, with few phosphohistone H3-positive cells being identified. Where division does occur within the epithelium it is restricted to the apical surface. The neurogenic placodes thus represent specialized ectodermal niches that generate neuroblasts over a protracted period.